Studi Tentang Pluralisme Dalam Islam Progresif di Indonesia - Nuha, Ulin (Jurnal Dewantara, 2020)
The term progressive Islam has only been in contemporary Islamic studies used by academics and activists since the last few years. This Progressive Islamic Movement also emerged as a cultural grounding movement, especially Islam Nusantara. For example, the Muslims who are affiliated to NU in general are those who come from villages, work as farmers, have an educational background in traditional pesantren (salaf) and have a strong adherence to tradition. Maintain ancestral traditions and as much as possible integrate religions and traditions that are harmonious and do not conflict with each other. Culture as a method of Islamic da'wah used to invite people to understand and obey all God's commands by using cultural approaches or the culture of the local community. So that it provides diversity and invites people to love Islam in ways that are not rigid and adapt to local culture so that Islam is no longer a rigid religion in spreading it. Kaku means practicing Islam does not have to use methods or methods of violence or blame other parties, but in a humanistic manner and strengthens it with the existing cultural acculturation.